Characterising radio sources in the Small Magellanic Cloud using citizen science and optical spectroscopy - De Beer, Gideon (Department of Astronomy, 2025)
For several years, the Small Magellanic Cloud (SMC) has been extensively studied in multiple wavelengths, revealing rich populations of radio sources within and beyond the nearby dwarf galaxy. With radio interfer-ometers' ever-increasing sensitivity and resolution, greater source populations will be discovered. Two regions of the SMC dwarf galaxy were observed using MeerKAT, with 10873 radio sources identified across them. In this dissertation, we characterise the radio source population of these two regions. This was approached using citizen science and optical spectroscopic follow-up. From the 10873 radio sources, 1429 were selected as subjects for classification in the citizen science project. This selection was based on the radio signal-to-noise ratio. The citizen science approach used information from the radio images, combined with optical cutouts from the SuperCOSMOS Sky Survey. The results show a high level of agreement among volunteer classi-fiers on questions concerning basic morphological characteristics. Around 63 per cent of all classifications show complete agreement between at least 5 classifiers in determining whether the displayed source was a radio point or an extended source and whether there is a likely optical counterpart aligned with the radio emission for the 1429 subjects. 41 radio sources were selected from the original 10873 for spectroscopy, by cross-matching the radio source list to the GAIA optical catalogue and making a magnitude cut. Optical spectroscopic follow-up of 23 sources from these 41 was conducted in November 2023. The reduced spectra from the observations were analysed to identify the optical sources, determine whether the optical and radio emissions were coincident, and identify what mechanism might be causing the radio emission if the optical source is considered likely to be the optical counterpart to the radio source. Characterisation revealed 13 stars, 3 eclipsing binaries and 2 nebulae. Between the two analysis methods, with their own independently se-lected source sample pools, 6 sources were found to overlap. The resultant analysis between the methods gave complementary source characterisation results. Approximately 912 radio sources have been characterised in total, at least by radio morphology and the likely presence of an optical counterpart, during this project.